Сто років української індоєвропеїстики - Конча, С.В. (Кам’яна доба України, 2010)
Стаття становить собою стислий нарис історії поглядів українських науковців ХХ ст. на питання зародження індоєвропейської спільноти та розвитку найдавніших носіїв індоєвропейських мов. Пропонується авторська оцінка основних концепцій. Paper represents a brief review of the history of opinions of Ukrainian scientists of the XX-th century in the concern of questions of origins of Indo-European entity and development of the earliest carriers of Indo-European languages. Own author’s evaluations of suggested concepts are s proposed.